Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12889-022-14068-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between overweight, obesity and sleep duration and related lifestyle behaviors is gender and educational stages dependent among children and adolescents aged 6-17 years: a cross-sectional study in Henan

Abstract: Background To investigate the associations between overweight, obesity and sleep duration and related lifestyle behaviors in children and adolescents at different gender and educational stages. Methods A cross-sectional study comprising 18723 children and adolescents with a stratified cluster sampling method of Henan Province was conducted in 2019. A self-reported questionnaire was used to collect the information about demographic characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Speci cally, individuals with shorter sleep durations, particularly females, exhibited higher values of BMI, body fat percentage, waist and hip circumferences, and fat mass index. [18, 19,20]. The relationship between decreased sleep duration and obesity can be understood through various mechanisms.…”
Section: Association Of Lifestyle and Medical Factors With Obesitymentioning
confidence: 99%
“…Speci cally, individuals with shorter sleep durations, particularly females, exhibited higher values of BMI, body fat percentage, waist and hip circumferences, and fat mass index. [18, 19,20]. The relationship between decreased sleep duration and obesity can be understood through various mechanisms.…”
Section: Association Of Lifestyle and Medical Factors With Obesitymentioning
confidence: 99%
“…Actigraphy was employed in the absence of a polysomnography machine since it is an examination that uses tools comparable to a clock (actigraph) [27]. But a study shows there is enough congruence between self-reported and objective assessments suggesting that studies using only questionnaires are also valid [27,28]. While all the publications included in this review was done to investigate the relationship between sleeping pattern and hypertension, different location, time, and different samples of adults and adolescents were included.…”
Section: [23] Amentioning
confidence: 99%